ORM in Dynamic Languages. - Richardson, Chris (Communications of the ACM, 2009)
The article discusses the use of object-relational mapping (ORM) in dynamic languages. An ORM framework allows developers to declaratively define the mapping between the object model and database schema and express database-access operations in terms of objects. The author examines an ORM framework called GORM (Grails Object Relational Mapping) for Groovy, which allows new program elements to be created at runtime. The article compares and contrasts GORM and Hibernate, an ORM framework popular with Java developers. Also discussed are executing queries and performing basic save, load, and delete operations on persistent objects.